KARAKTERISASI 3D SUBSTRAT BENTIK PERAIRAN KARANG PULAU BONETAMBUNG MAKASSAR - Selamat, Muhammad Banda; Muhiddin, Amir Hamzah; Ukkas, Marzuki (Hasanuddin University, 2014)
The objective of this study is to characterize benthic substrate of Bonetambung reef area using worldview 2 highresolution satellite imagery. About 14.273 depth spot were deploy to build bathimetric model of the study area. The correlation of pixel radiance value from satellite imagery and depth value from field measurement werebecame the basis to classify geomorphologic zone of shallow water area up to 7 meter depth. Between threeinterpolator tested, the natural neighbor interpolator has produced the best bathymetric model with root meansquare error 0.3 meter and benthic substrate coverage model with thematic accuracy 62%. These approach beable to recognize four substrate type in general, such as sand, seagrass, rubble and coral. Geomorphicsegmentation based on bathymetric profile and radiance value of worldview 2 imagery may also maps the reefflat, reef slope and lagoon area hence may support the benthic substrate modeling. This study showed us apotential technic to develop a modelling for juvenile fish transport at Bonetambung coral waters.Key words: benthic substrate bathymetry, worldview imagery, thematic accuracy